Pengaruh Struktur Modal,Kebijakan Hutang,Ukuran Perusahaan dan Kesempatan Investasi Terhadap Nilai Perusahaan Pada Perusahaan Minyak dan Gas Bumi - Alfrendy Damana Sembiring; Revian Liandro Damanik; Patrick Fernando; Yeni Ariesa; M. Shabri Abd. Majid (Politeknik Ganesha Medan, 2023)
The purpose of this research is to provide a determination regarding the influence exerted by the indicators of Capital Structure, Debt Policy, Company Size, and Investment Opportunities on the value of oil and gas companies. This study applies a descriptive quantitative method. The Indonesia Stock Exchange and Idn Financial are the sources of applied data, and also use Eviews 12 analysis as the analysis process. By using 10 company observations that were used as samples. So the conclusion from the result of testing the hypothesis simultaneously found the firm value that receives influence from Capital Structure, Debt Policy, Company Size, and Investment Opportunities. However, the results of the hypothesis test illustrate that Capital Structure and Investment Opportunities have a positive and significant influence on firm value, on firm value, but in fact the Debt Policy and Company Size are the opposite.